Direito eco-evolutivo: níveis de observação para decisões na hipercomplexidade - Tybusch, Jerônimo Siqueira (Universidade do Vale do Rio do Sinos, 2007)
The present work intends to develop the idea of an Eco-Evolution Right based on levels of perceptions capable to make possible decisions in Hyper-Complexity ambient conflicts. The ecological communication provokes relations of complementarities, competition and antagonism in the role of the legal institutions, promoting permanent, similar interactions of reorganization of an ecosystem. Through the transposition of originary categories of biology (heterotrophy, parasitism, mutations), physics (thermodynamic) and chemistry (entropy), as well as of the use of metaphors of the System of the Art, language and Semiotics improved understandings of the social phenomenon will be made possible in that it refers to the high complexity of the ambient problems ranks to the together decision to the Right. For in such a way, they consider it construction of seven levels of comment, seven types of microscopically lenses, which will use the responsible legal agencies for decisions about of these situations. Of this form, it p
Keywords: decisão; hipercomplexidade; observação; direito eco-evolutivo; decision; hyper-complexity; observation; eco-evolution right; Ciências Sociais Aplicadas